Les crimes et châtiments emblématiques à travers l’exemple du drapeau médiéval - Julien De Palma (Criminocorpus)
Medieval sources often mentioned violence against flags, in a military context or not: these practices can be explained by the importance attached by medieval justice to visual elements in the exercise of punishment. Flags bore emblems, that is, signs that stated the identity of a person, so they could be regarded as a projection, a substitute, of their owners. This special status is evidenced by practice and official documentation: for example, the dukes of Burgundy of House Valois insisted, in their military orders, on the importance, and the obligation, for soldiers, of respecting and obeying flags. As a consequence, violence against flags could be regarded as a form of punishment in absentia: the exhibition of flags seemed very much like a pillorying of their owner, and their destruction a killing.